2008
DOI: 10.1016/j.juro.2008.08.037
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of Seminal Vesicle Involvement Found at Prostatectomy and the Effects of Adjuvant Radiation: Data From Southwest Oncology Group 8794

Abstract: Purpose From the randomized study SWOG 8794, we evaluated the effect of seminal vesicle involvement on outcomes and whether those patients benefited from post prostatectomy adjuvant radiation therapy. Materials and Methods SWOG 8794 randomized high risk (SV+ and/or capsular penetration and/or positive margins) post prostatectomy patients to radiation versus observation. 431 subjects with pathologically-advanced prostate cancer were randomized Results Median follow up is 12.2 years. A total of 139 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 13 publications
2
40
1
1
Order By: Relevance
“…At the time of initial publication there was a recurrence-free and PSA relapsefree benefit for the addition or radiation therapy and a trend for an overall survival benefit that became significant with longer follow-up and more deaths (23). At a median follow-up of 12.2 years, this trial showed a benefit for patients with seminal vesicle involvement who received radiation therapy, but no there was no mention of benefit for patients who only had positive surgical margins (24). A European trial focused on men with pathologically stage T3 N0 (extension through the prostate capsule and/or seminal vesicle involvement) prostate cancer, who had undergone radical prostatectomy and had an undetectable PSA level after surgery (6).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…At the time of initial publication there was a recurrence-free and PSA relapsefree benefit for the addition or radiation therapy and a trend for an overall survival benefit that became significant with longer follow-up and more deaths (23). At a median follow-up of 12.2 years, this trial showed a benefit for patients with seminal vesicle involvement who received radiation therapy, but no there was no mention of benefit for patients who only had positive surgical margins (24). A European trial focused on men with pathologically stage T3 N0 (extension through the prostate capsule and/or seminal vesicle involvement) prostate cancer, who had undergone radical prostatectomy and had an undetectable PSA level after surgery (6).…”
Section: Discussionmentioning
confidence: 93%
“…(5,6,23,24). However, most patients in those trials also had capsular invasion or extracapsular extension, or seminal vesicle invasion (pT3); so the trials lack sufficient power to draw any firm conclusions regarding the pT2 subset.…”
Section: Discussionmentioning
confidence: 99%
“…A subset analysis of the South West Oncology Group 8794 trial evaluated the effect of SVI on outcomes after post-prostatectomy adjuvant RT. With a median follow up of 12.2 years the 10-year BCR and overall survival was only 22% and 61% 25 . However, patients with SVI who received adjuvant radiation showed an improvement in 10-year BCR from 12% to 36%, and overall survival from 51% to 71%.…”
Section: Discussionmentioning
confidence: 94%
“…6 The effectiveness of adjuvant radiation therapy in preventing PSA relapse and metastasis has been described in several retrospective 7,8,9 and prospective 10,11 studies, with some studies also attempting to determine factors that would predispose patients to a positive response to adjuvant therapy. [12][13][14] The long-term follow-up of the Southwest Oncology Group adjuvant radiation therapy trial (SWOG 8794/RTOG 9019) with 12-year data 15 16 Given the modest duration of this study's follow-up, the long-term risk of metastatic disease is not yet known.…”
Section: Resultsmentioning
confidence: 99%